An interactive multimedia music repository over the internet - Ang, Minni; Tee, Elok Robert; Othman, Abu Talib (Masters of Library and Information Science Unit, Faculty of Computer Science and Information Technology, University of Malaya, 1997)
The aim of the Interactive Multimedia Music Repository project is to create a Malaysian music web site, into which any Internet user may surf to discover the kinds of music found in the country. The repository serves as a source of Malaysian musical reference and provides formal distance learning courses conducted on the same subject through the Internet. The multimedia information content implicit in such an application needs to be properly designed, implemented and managed for remote multimedia database access. The paper presents the criteria designed to guide the construction of the music repository database.